Northwest of Suez : The 1956 Crisis and the IMF - Boughton, James (IMF Working Papers; Working Paper ;, 2000)
Egypt's nationalization of the Suez Canal in 1956 and the failed attempt by France, Israel, and Britain to retake it by force constituted a serious political crisis with significant economic consequences. For the United Kingdom, it engendered a financial crisis as well. That all four of the combatants sought and obtained financial assistance from the IMF was highly unusual for the time and had a profound effect on the development of the Fund. This case study illustrates the complexities in isolating the current account as the basis for determining a balance of payments 'need' and shows that the speculative attack on sterling-and the Fund's response to it-were remarkably similar to financial crises in the 1990s.